2004
DOI: 10.1007/978-3-540-30135-6_86
|View full text |Cite
|
Sign up to set email alerts
|

Non-rigid Atlas to Subject Registration with Pathologies for Conformal Brain Radiotherapy

Abstract: Abstract. Warping a digital atlas toward a patient image allows the simultaneous segmentation of several structures. This may be of great interest for cerebral images, since the brain contains a large number of small but important structures (optical nerves, grey nuclei, etc.). One important application is the conformal radiotherapy of cerebral tumor, where a precise delineation of all these structures is required. However, in this case, the variability induced by the tumor or a surgical resection, that are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…As the deformation is only based on contours of interest, the probability of registration errors increases more we are far from these contours. As far as we know, most of the existing methods for registration of images with space-occupying tumors are either surface-based [10,12,15,35] or voxel-based [2,4,[6][7][8]36] approaches. However, in our opinion it is worth to study how to combine the advantages of both approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As the deformation is only based on contours of interest, the probability of registration errors increases more we are far from these contours. As far as we know, most of the existing methods for registration of images with space-occupying tumors are either surface-based [10,12,15,35] or voxel-based [2,4,[6][7][8]36] approaches. However, in our opinion it is worth to study how to combine the advantages of both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods [7][8][9] locally adapted the elasticity of the transformation, rather than modeling the deformation induced by the tumor, in a way that large deformations induced by the tumor can be captured. To avoid tumor segmentation, Duay et al in [7] did not use a special scheme to preserve the regularity of the transformation in the areas where the images differ topologically (e.g., inside the tumor).…”
Section: Survey Of Registration Methods For Brain Mr Images With Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second term performs a regularization of the temporal derivative of the displacement field, similar to a fluid regularization of the velocity field in fluid mechanics. By locally weighting this "fluid" regularization with a scalar field k, [8] showed that the algorithm can be rendered robust with respect to potential pathologies in the subject image.…”
Section: Incorporating Statisticsmentioning
confidence: 99%